An Adaptive Turbo Decoding Algorithm - Li Jianping; Cai Chaoshi; Feng Yunfei (2008 4th International Conference on Wireless Communications, Networking and Mobile Computing, 2008)
The extrinsic information and the received systematic observations exert different influence on decision-making with the change of SNR values for turbo iterative decoding. By multipling a weighted coefficient for the priori information, this paper proposed a novel adaptive iterative soft decoding algorithm for turbo codes, which alters the proportion of the extrinsic information and the received systematic observations in the soft output values of turbo decoding. In this way, turbo decoding can trace the changes of channel and obtain improved performance. Simulation results show that the proposed scheme can lower the error floor of turbo codes.